KNOWLEDGE, ATTITUDE AND PERCEPTION OF TERTIARY EDUCATION STUDENTS TOWARDS PEOPLE LIVING WITH HIV/AIDS IN GOMBE STATE - ABDU, MURTALA MUHAMMAD; BOJUDE, ADAMU D.; ABDULLAHI, SALIHU; SANI, SHUAIBU; UMAR, DANLADI, M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
Knowledge, attitudes and perceptions concerning HIV/AIDS is one of the fundamental steps in the fight against the illness. Young people such as students are most susceptible to the disease because they are most sexually active and engage in risky practices due to lack of adequate information. Therefore, assessing their knowledge, attitudes and perceptions will help in designing a suitable prevention strategy. The aim of this study is to explore the level of knowledge, attitude and perception of students in higher institutions of learning towards HIV/AIDS and people living with HIV/AIDS (PLWHA). Through a cross-sectional study and stratified random sampling, we administered a pilot-tested standard questionnaire to assess the HIV/AIDS knowledge, attitudes and perceptions of 356 tertiary education students aged 18-46 years in Gombe State, Nigeria. Data were analyzed using STATA 10 statistical software. Four hundred students were approached to complete the questionnaires, 44 did not return their questionnaires. The mean age of the 356 participating students was 23.09±4.86 years (SD=4.86). The male to female ratio was 2:1. Over 90% of the students were aware of HIV/AIDS, and mass media (39.6%) and teachers (38.5%) were their major sources of information about disease. More than half of the students (60.6%) were willing to live with PLWHA and about two third of the (69.5%) wouldn’t like students living with HIV/AIDS (SLWHA) to be educated in a separate school and (80%) would want all students to go for annual mandatory HIV testing. Although, most of the students have satisfactory knowledge about HIV/AIDS, and positive attitude and perception towards PLWHA, some misconceptions still exist among the students about the source of acquiring the disease.Educational programs and strategies involving schools and youth’s networks should be employed to overcome these misconceptions.